Exploring advanced and sustainable bioaugmentation-enhanced ultrafiltration processes for the removal of emerging contaminants - Ye, Tingming; Wang, QingJi; Qi, Jing; Ma, Baiwen; Lyu, Tao; Hu, Chengzhi; Ulbricht, Mathias; Liu, Huijuan (Elsevier, 2025)
The development of cost-effective and sustainable water treatment technologies is crucial for supporting the water sector and the public in achieving global sustainable development goals (SDG 6) and carbon neutrality targets. Ultrafiltration (UF), known for its compactness, relatively high performance, and ease of operation, has been widely deployed in water treatment. However, its limitations in removing some emerging contaminants (ECs) and membrane fouling issues have hindered its broader application. This study investigated the incorporation of bioaugmented filtration into conventional UF processes to enhance ECs removal and mitigate membrane fouling during the treatment of real drinking water sources. In addition to effectively removing microorganisms (eukaryotes and bacteria), polysaccharides (13.9%), and inorganic pollutants (CaCO3, MgO, SiO2, and Al2O3), the proposed approach also demonstrated superior removal (4.6%–100.0%) of four target ECs (atenolol, carbamazepine, trimethoprim, and sulfamethoxazole) compared to direct UF process (1.5%–47.5%). After 56 days of operation, the bioaugmented pre-treatment significantly reduced transmembrane pressure (TMP) by 80.2% compared to the direct UF process. Mechanisms studies further reassured that ECs removal followed oxidation during bioaugmentation pre-treatment. The time-of-flight secondary ion mass spectrometry with in-depth analysis capability (around 5 nm) revealed that the UF membrane primarily removed atenolol through adsorption. The toxicity prediction results of typical ECs and their degradation intermediates indicated a significant reduction in ecological risk for most intermediates. The findings from this work demonstrate the feasibility of using low-carbon and few-chemical water treatment technologies to secure drinking water quality.
Keywords: 4004 Chemical Engineering; 40 Engineering; 4011 Environmental Engineering; 6 Clean Water and Sanitation; Chemical Engineering; 34 Chemical sciences